Efficacy of the Da Vinci surgical system in colorectal surgery comparing with traditional laparoscopic surgery or open surgery: A meta-analysis. (5th October 2016) - Huang, Jintang; Zhang, Zhongmin; Wang, Shaoyong
In order to compare the curative effect of the Da Vinci surgical system (DVSS) with laparoscopic surgery (LS) or open surgery for colorectal resection, literature search was conducted in PubMed, Excerpt Medica Database (Embase), and Cochrane library up to January 15, 2016. Odds ratio (OR) and weighted mean difference with their corresponding 95% confidence intervals were used as effect size for evaluation of different outcomes. In total, 10 studies consisting of 2767 patients were included for the meta-analysis. As a result, there were no significant differences between DVSS and LS/open surgery in the long-term oncologic outcomes ( p > 0.05). However, DVSS achieved a significantly lower length of hospital stay and estimated blood loss (EBL), but a longer operation time. Moreover, DVSS showed a significantly reduced conversion to open surgery than LS (OR = 0.19, 95% confidence interval: 0.08–0.48). Subgroup analysis indicated that DVSS had different results in rectal adenocarcinoma and colon cancer subgroups on outcomes of conversion to open surgery and operation time. DVSS is superior to LS/open surgery in length of hospital stay and EBL, but needs longer operation time. Long-term outcomes of DVSS are comparable with the other approaches. From long-term perspective, DVSS has an equivalent effect to the other two techniques.